Electrical Properties of A Novel Solid Biopolymer Electrolyte based on Algi-nate Incorporated with Citric Acid - Ahmad Fuzlin, Ahmad Faizrin; Ismail, Noor Syahida; Nagao, Yuki; Samsudin, Ahmad Salihin (UI Scholars Hub, 2019)
In the present study, a novel solid biopolymer electrolyte (SBE) system is introduced by doping citric acid into alginate polymer. A sample of the alginate-citric acid SBE system was prepared via a solution casting technique. Using electrical impedance spectroscopy (EIS), the electrolytes of alginate-citric acid analyzed from 5 Hz to 1 MHz achieved the highest conductivity at 20 wt.% of 5.49 × 10-7 S cm-1. The temperature dependence of various citric acid amounts obeyed the Arrhenius rule with R2 1, where all SBE systems were thermally activated with increasing temperature. The dielectric studies of the alginate-citric acid SBE system showed non-Debye behavior based on data measured using complex permittivity (ε*) and complex electrical modulus (M*) at selected temperature, where no single relation was found in the new biopolymer electrolyte system.